Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To determine which of the given functions is an odd function, let's recall the definition of an odd function. A function [tex]\(f(x)\)[/tex] is considered odd if it satisfies the condition [tex]\( f(-x) = -f(x) \)[/tex] for all [tex]\( x \)[/tex] in its domain.
### Step-by-Step Analysis:
1. First Function: [tex]\( f(x) = 3x^2 + x \)[/tex]
[tex]\[ f(-x) = 3(-x)^2 + (-x) = 3x^2 - x \][/tex]
Compare it with [tex]\( -f(x) \)[/tex]:
[tex]\[ -f(x) = -(3x^2 + x) = -3x^2 - x \][/tex]
Since [tex]\( 3x^2 - x \neq -3x^2 - x \)[/tex], [tex]\( f(x) = 3x^2 + x \)[/tex] is not an odd function.
2. Second Function: [tex]\( f(x) = 4x^3 + 7 \)[/tex]
[tex]\[ f(-x) = 4(-x)^3 + 7 = -4x^3 + 7 \][/tex]
Compare it with [tex]\( -f(x) \)[/tex]:
[tex]\[ -f(x) = -(4x^3 + 7) = -4x^3 - 7 \][/tex]
Since [tex]\( -4x^3 + 7 \neq -4x^3 - 7 \)[/tex], [tex]\( f(x) = 4x^3 + 7 \)[/tex] is not an odd function.
3. Third Function: [tex]\( f(x) = 5x^2 + 9 \)[/tex]
[tex]\[ f(-x) = 5(-x)^2 + 9 = 5x^2 + 9 \][/tex]
Compare it with [tex]\( -f(x) \)[/tex]:
[tex]\[ -f(x) = -(5x^2 + 9) = -5x^2 - 9 \][/tex]
Since [tex]\( 5x^2 + 9 \neq -5x^2 - 9 \)[/tex], [tex]\( f(x) = 5x^2 + 9 \)[/tex] is not an odd function.
4. Fourth Function: [tex]\( f(x) = 6x^3 + 2x \)[/tex]
[tex]\[ f(-x) = 6(-x)^3 + 2(-x) = -6x^3 - 2x \][/tex]
Compare it with [tex]\( -f(x) \)[/tex]:
[tex]\[ -f(x) = -(6x^3 + 2x) = -6x^3 - 2x \][/tex]
Since [tex]\( -6x^3 - 2x = -6x^3 - 2x \)[/tex], [tex]\( f(x) = 6x^3 + 2x \)[/tex] is indeed an odd function.
### Conclusion:
Out of the given functions, the only one that satisfies the condition for being an odd function is [tex]\( f(x) = 6x^3 + 2x \)[/tex]. Therefore, the correct answer is:
[tex]\[ \boxed{f(x) = 6x^3 + 2x} \][/tex]
### Step-by-Step Analysis:
1. First Function: [tex]\( f(x) = 3x^2 + x \)[/tex]
[tex]\[ f(-x) = 3(-x)^2 + (-x) = 3x^2 - x \][/tex]
Compare it with [tex]\( -f(x) \)[/tex]:
[tex]\[ -f(x) = -(3x^2 + x) = -3x^2 - x \][/tex]
Since [tex]\( 3x^2 - x \neq -3x^2 - x \)[/tex], [tex]\( f(x) = 3x^2 + x \)[/tex] is not an odd function.
2. Second Function: [tex]\( f(x) = 4x^3 + 7 \)[/tex]
[tex]\[ f(-x) = 4(-x)^3 + 7 = -4x^3 + 7 \][/tex]
Compare it with [tex]\( -f(x) \)[/tex]:
[tex]\[ -f(x) = -(4x^3 + 7) = -4x^3 - 7 \][/tex]
Since [tex]\( -4x^3 + 7 \neq -4x^3 - 7 \)[/tex], [tex]\( f(x) = 4x^3 + 7 \)[/tex] is not an odd function.
3. Third Function: [tex]\( f(x) = 5x^2 + 9 \)[/tex]
[tex]\[ f(-x) = 5(-x)^2 + 9 = 5x^2 + 9 \][/tex]
Compare it with [tex]\( -f(x) \)[/tex]:
[tex]\[ -f(x) = -(5x^2 + 9) = -5x^2 - 9 \][/tex]
Since [tex]\( 5x^2 + 9 \neq -5x^2 - 9 \)[/tex], [tex]\( f(x) = 5x^2 + 9 \)[/tex] is not an odd function.
4. Fourth Function: [tex]\( f(x) = 6x^3 + 2x \)[/tex]
[tex]\[ f(-x) = 6(-x)^3 + 2(-x) = -6x^3 - 2x \][/tex]
Compare it with [tex]\( -f(x) \)[/tex]:
[tex]\[ -f(x) = -(6x^3 + 2x) = -6x^3 - 2x \][/tex]
Since [tex]\( -6x^3 - 2x = -6x^3 - 2x \)[/tex], [tex]\( f(x) = 6x^3 + 2x \)[/tex] is indeed an odd function.
### Conclusion:
Out of the given functions, the only one that satisfies the condition for being an odd function is [tex]\( f(x) = 6x^3 + 2x \)[/tex]. Therefore, the correct answer is:
[tex]\[ \boxed{f(x) = 6x^3 + 2x} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.